Effect of Diversion Ileostomy on the Occurrence and Consequences of Chemotherapy-Induced Diarrhea. Issue 3 (March 2016) - Robertson, Jason P.; Wells, Cameron I.; Vather, Ryash; Bissett, Ian P.
Abstract : BACKGROUND: The benefits of adjuvant chemotherapy in the treatment of colorectal cancer are well established. Chemotherapy-induced diarrhea is a common adverse effect of these regimens. The occurrence of chemotherapy-induced diarrhea not only directly affects patient health but may also compromise treatment efficacy because of consequent dosing alterations or discontinuation. OBJECTIVE: This study aimed to investigate the effect of diverting loop ileostomy during chemotherapy on the occurrence and consequences of chemotherapy-induced diarrhea. DESIGN: This was a retrospective evaluation of a prospective surgical database. SETTINGS: This was a single-institution retrospective study. PATIENTS: All patients receiving curative adjuvant chemotherapy after anterior resection for colorectal cancer at Auckland Hospital from 2002 to 2013 were retrospectively evaluated. MAIN OUTCOME MEASURES: Patient-, perioperative-, and chemotherapy-related variables were collected. Chemotherapy-induced diarrhea occurrence was graded according to National Cancer Institute Common Terminology Criteria for Adverse Events. Logistic regression analysis was performed to identify independent predictors for chemotherapy-induced diarrhea occurrence, treatment modifications, and hospital admission. RESULTS: A total of 109 identified patients received 691 chemotherapy cycles; 84% of patients with a diverting ileostomy experienced chemotherapy-induced diarrhea compared with 47% in those who were not defunctioned ( p < 0.01). On logistic regression analysis, the presence of a diverting ileostomy during chemotherapy was an independent predictor of chemotherapy-induced diarrhea grade 3 or higher (OR, 13.6 (95% CI: 1.2–150.9); p = 0.02), the need for a dosing reduction (OR, 4.0 (95% CI: 1.3–12.4); p = 0.02), and the need for any modification in the chemotherapy regimen (OR, 3.4 (95% CI: 1.2–9.6); p = 0.02). LIMITATIONS: This study is limited by its retrospective design, potentially limiting the accuracy of chemotherapy-induced diarrhea grade reporting. CONCLUSIONS: The presence of an ileostomy during adjuvant chemotherapy is a predictor of severe chemotherapy-induced diarrhea and the need for modifications in the chemotherapy regimen. This may have important consequences for long-term survival. Prospective investigation is needed to further assess the impact of diverting ileostomy on the delivery of chemotherapy and oncologic outcomes.